Pressure driven MHD instabilities in the intrinsic and externally enhanced magnetic stochastic region of LHD. (30th July 2015) - Ohdachi, S.; Suzuki, Y.; Tsuchiya, H.; Watanabe, K.Y.; Sakakibara, S.; Narushima, Y.; Du, X.D.; Ming, T.F.; Furukawa, M.; Toi, K.; Yamada, H.
Abstract: Characteristics of the pressure-driven magnetohydrodynamic (MHD) instabilities in the magnetic stochastic region, which surrounds the core plasma of the large helical device, are studied. There appear MHD instabilities with an amplitude of 10 −4 of the toroidal magnetic field. From the mode number of activities (poloidal/toroidal mode number, 1/2, 2/4), the location of the corresponding rational surface is near the LCFS or definitely outside the LCFS. Parameter dependence of the saturation level is examined for evaluation of the impact of MHD activities. The saturation level increases with increase of the pressure gradient and decreases with decrease of the local collisionality. In order to study the dependence on the magnetic field structure, experiments with the resonant magnetic field perturbation (RMP) with m / n = 1/1 were conducted. While the magnetic island is formed around the rotational transform surface, the magnetic field structure outside the nested region is disturbed. Amplitude of m / n = 2/3 and 2/4 modes are reduced by this resonant magnetic pertubation (RMP) field when the normalized RMP coil current exceeds 0.3 kA T −1 . Since the local pressure gradient and the local plasma parameters are not changed by the RMP, this reduction is caused by the change of the magnetic field structure itself.